Crane: A Tool for Reliability Analysis with Different Coverage Models - Xiang, Jianwen; Liu, Lang; Yang, Ming; Zhou, Siwei; Ye, Luyao; Weng, Caisheng; Zhao, Dongdong; Tian, Jing (Anais do Latin-American Symposium on Dependable Computing (LADC); 2018: Anais do VIII Latin-American Symposium on Dependable Computing, 2018)
In this paper, we introduce Crane, a new software tool for reliability analysis of systems subject to perfect and imperfect fault coverage. Crane supports qualitative and quantitative analysis of traditional fault trees, imperfect fault coverage model (IFCM), and irrelevancy coverage model (ICM). ICM is a new coverage model which can detect and isolate irrelevant components in addition to faulty components, such that the not-covered faults of the irrelevant components will not affect the system anymore. The analysis of ICM is not available in the third-party tools. A generalized multiple-valued decision diagram algorithm is implemented in Crane, and it can be used to analyze both IFCM and ICM. Crane supports graphic and text input modes. Experimental results on some benchmark fault trees show that Crane outperforms some existing tools in terms of the efficiency for evaluation of minimal cut sets, and it can also be used to analyze the reliability of IFCM and ICM in an efficient way.